Defining the art product: a network perspective. (15th May 2020) - Wickham, Mark; Lehman, Kim; Fillis, Ian
Abstract : Purpose: This paper explores the nature of art as a product through a network perspective, accounting for key contributing stakeholders in shaping its essence. Design/methodology/approach: This study adopted a qualitative data collection and analysis design and is centred on a series of face-to-face interviews with established Australian visual artists. Findings: Results support the notion of an art product shaped by interconnections and interdependencies of actors in the art market. In particular, attention is paid to the roles of actors in conceptual, production and distribution networks. Research limitations/implications: Although there are idiosyncrasies that (in part) define the Australian art market context, the issues identified here are nonetheless useful in determining the nature of the interconnectedness of the art market in other similar Western contexts. Many Australian artists have achieved similar recognition and status to other established artists elsewhere. Future cross-cultural comparative research should be carried out in order to assess this relationship in the longer term. Practical implications: Artists at different stages of their careers can transfer the findings of this research into the development of a series of relevant strategies and tactics for developing their art and culture products more effectively. Originality/value: Although philosophical assessments of art as a product have been carried out elsewhere, there is a lack of evaluation from an art versus marketplace lens in considering the perspectives of interested stakeholders